School Inclusion and Mathematics: Use of the PhET Simulator as Assistive Technology for Students with ASD (Interdisciplinary Studies Journal, 2024)
The search for strategies and resources that can effectively contribute to the teaching process of students with special educational needs, notably those diagnosed with Autism Spectrum Disorder (ASD), is fundamental to foster inclusive and equitable education. The article aims to explore the potential of the PhET assistive technology simulator in teaching fractions, aiming to enhance the inclusion of students with ASD in the mathematical scenario. The research was conducted at a full-time public school in the city of Sobral - CE. Participants included a science teacher, two students with ASD, and 24 sixth-grade students. The method adopted was action research with a qualitative and descriptive applied nature. Data collection involved application of activities, use of the PhET simulator, and observation. The research results showed a positive response from students to the use of PhET Simulators in performing the proposed activities. Therefore, the findings not only suggest the effectiveness of the PhET simulator but also point to the possibility of its replication in other educational contexts, thus contributing to the advancement of inclusive and technologically assisted practices in mathematics education.
Keywords: School Inclusion; Simulators; Assistive Technology; Autism Spectrum Disorder